UPAYA PENGELOLA TAMAN BACAAN MASYARAKAT DALAM MEMPERKUAT MINAT MEMBACA (Studi Kasus TBM Silayung Desa Ciburuy Kecamatan Padalarang) - Rini Rahayu; Novi Widiastuti,M.Pd (Comm-Edu (Community Education Journal), 2018)
This research is motivated by the problems found in TBM Silayung, namely the ratio between the number of residents with library visitors or readers should be able to reach the number one to ten people per day. While the ratio for the West Java at this time still in the range of one to tens of thousands. The purpose of this study this (1) To know the process of managing TBM Silayung in growing the reading culture. (2) To know management strategy of TBM Silayung in growing the reading culture. (3) To know the reader's response to the management of TBM Silayung.Theories used in this research include the concept of TBM, the concept of reading, the concept of management and the concept of PLS. The method used is qualitative descriptive approach and with a qualitative method. Data collection techniques used interviews and observations. Research location in TBM Silayung Desa Ciburuy, which is the respondent in this research manager, secretaries TBM, and five representatives from TBM visitors.Based on the research result that TBM Silayung has tried to run TBM according to its role. But still needs to be improved again in the form of programs that are creative and interesting